SAFETY AND EFFICACY OF EPLERENONE IN PATIENTS AT HIGH RISK FOR HYPERKALEMIA AND/OR WORSENING RENAL FUNCTION. ANALYSES OF THE EMPHASIS-HF STUDY SUBGROUPS (EPLERENONE IN MILD PATIENTS HOSPITALIZATION AND SURVIVAL STUDY IN HEART FAILURE) - R. Eschalier; J.J.V. McMurray; K. Swedberg; D.J. Veldhuisen van; H. Krum; S.J. Pocock; H. Shi; J. Vincent; P. Rossignol; F. Zannad; B. Pitt (Столичная издательская компания, 2015)
Translation articles: R. Eschalier, J.J.V. McMurray, K. Swedberg, D.J. van Veldhuisen, H. Krum, S.J. Pocock, H. Shi, J. Vincent, P. Rossignol, F. Zannad, B. Pitt, for the EMPHASIS-HF Investigators "Safety and Efficacy of Eplerenone in Patients at High Risk for Hyperkalemia and/or Worsening Renal Function. Analyses of the EMPHASIS-HF Study Subgroups (Eplerenone in Mild Patients Hospitalization And SurvIval Study in Heart Failure)"  J Am Coll Cardiol 2013;62(17):1585-93; http://dx.doi.org/10.1016/j.jacc.2013.04.086